IMPLEMENTASI PERMENDES NO. 6 TAHUN 2020 DALAM PRIORITAS PENGGUNAAN DANA DESA TAHUN 2020 : (Studi Kasus Desa Jambeyan Kecamatan Sedan Kabupaten Rembang) - Widiarseno, Dandung; Rinayuhani, Tri Ratna; Santosa (MAJAPAHIT POLICY, 2022)
In the Covid-19 pandemic in Indonesia, many aspects have changed, especially the government aspect. Governmentrequired to issue the latest policy regarding handling the Covid-19 pandemic itself. In the village ministry, village ministryissued the latest policy, namely Village Minister Regulation No. 6 of 2020, which was not followed up by the village government, in this case the village governmentJambeyan issued several policies. The benefit of this research is that it provides information for knowing and analyzingImplementation of Village Ministerial Decree no. 6 of 2020 in Priority Use of Village Funds in 2020 in Jambeyan Village, Sedan District, RegencyRembang. If we relate it to Merilee S Grindle's theory of policy implementation, there are six aspects that need to be looked at, from the six aspects:conveyed that the theory of policy implementation is very related.Based on research results obtained through several informants, the implementation of Village Minister Regulation No. 6 of 2020 is a priorityuse of village funds in 2020 in Jambeyan village with program efforts that can create good conditions. Results from researchproves that the people of Jambeyan village are satisfied with the efforts of the Jambeyan village government in issuing policiesrelated to village regulation number 6 of 2020.